Wideband sound absorption of a double-layer microperforated panel with inhomogeneous perforation - Putra, Azma; Mosa, Ali Ibrahim; Jameel, Esraa Al-Amer; Ramlan, Roszaidi (Elsevier Ltd, 2020)
Micro-perforated panel (MPP) absorber is increasingly gaining popularity as an alternative sound absorber in buildings compared to the well-known synthetic porous materials. A single MPP has a typical feature of a Helmholtz resonator with a high amplitude of absorption but a narrow absorption frequency bandwidth. To improve the bandwidth, a single MPP can be cascaded with another single MPP to form a double-layer MPP. This paper proposes the introduction of inhomogeneous perforation in the double-layer MPP system (DL-iMPP) to enhance the absorption bandwidth of a double-layer MPP. Mathematical models are proposed using the equivalent electrical circuit model and are validated with experiments with good agreement. It is revealed that the DL-iMPP produces a wider half-absorption bandwidth compared to the conventional homogeneous double-layer MPP. The absorption bandwidth to higher frequencies can be effectively controlled by reducing the air cavity between the iMPPs and to the lower frequencies by increasing the back cavity depth at the second layer.